Silica dynamics in a pampean lake (Lake Chascomús, Argentina) - Miretzky, Patricia (2004)
Silica dynamics in a pampean lake, Lake Chascomús (Chaco-Pampa plain, Argentina) is described. Pampean lakes are shallow alkaline ecosystems, with circulation pattern corresponding to polymictic lakes, due to the nearly continuous vertical mixing that promotes a high concentration of suspended particulate matter and low transparency. A silica budget was calculated in Lake Chascomús in 1999?2000 using a one-box model that constitutes the first one for a shallow pampean lake. In general terms, the dissolved silica in Lake Chascomu´s contributed by streams and groundwater, the latter responsible for 70% of the incoming dissolved silica, was able to support the diatom production development. However, in the algal bloom period (spring and summer), the winter input contributed by the streams and groundwater was insufficient, and therefore, an extra source of dissolved silica was necessary. Dissolution of silicate mineral phases, or silica desorption from metallic oxides might provide the dissolved silica needed for the seasonal increase in diatom abundance. Silica dynamics in a pampean lake, Lake Chascomús (Chaco-Pampa plain, Argentina) is described. Pampean lakes are shallow alkaline ecosystems, with circulation pattern corresponding to polymictic lakes, due to the nearly continuous vertical mixing that promotes a high concentration of suspended particulate matter and low transparency. A silica budget was calculated in Lake Chascomús in 1999?2000 using a one-box model that constitutes the first one for a shallow pampean lake. In general terms, the dissolved silica in Lake Chascomu´s contributed by streams and groundwater, the latter responsible for 70% of the incoming dissolved silica, was able to support the diatom production development. However, in the algal bloom period (spring and summer), the winter input contributed by the streams and groundwater was insufficient, and therefore, an extra source of dissolved silica was necessary. Dissolution of silicate mineral phases, or silica desorption from metallic oxides might provide the dissolved silica needed for the seasonal increase in diatom abundance. Silica dynamics in a pampean lake, Lake Chascomús (Chaco-Pampa plain, Argentina) is described. Pampean lakes are shallow alkaline ecosystems, with circulation pattern corresponding to polymictic lakes, due to the nearly continuous vertical mixing that promotes a high concentration of suspended particulate matter and low transparency. A silica budget was calculated in Lake Chascomús in 1999?2000 using a one-box model that constitutes the first one for a shallow pampean lake. In general terms, the dissolved silica in Lake Chascomu´s contributed by streams and groundwater, the latter responsible for 70% of the incoming dissolved silica, was able to support the diatom production development. However, in the algal bloom period (spring and summer), the winter input contributed by the streams and groundwater was insufficient, and therefore, an extra source of dissolved silica was necessary. Dissolution of silicate mineral phases, or silica desorption from metallic oxides might provide the dissolved silica needed for the seasonal increase in diatom abundance.